Amaurosis Fugax and Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Amaurosis fugax, a sudden, transient monocular loss of vision resolving in 5 to 10 minutes, is reported in five teenagers from the British Columbia's Children's Hospital, Vancouver, BC, and The Hospital for Sick Children, Toronto, Canada.